Pengaruh Efikasi Diri, Pemberian Reward, Fasilitas Belajar, Disiplin Belajar Dan Lingkungan Keluarga Terhadap Prestasi Belajar Siswa Pada Mata Pelajaran Ekonomi Kelas X Ips Sma Negeri 4 Payakumbuh - Dwiyanti, Tiari J; Wahyuni, Sri; Eprillison, Vivina (Universitas PGRI Sumatera Barat, 2022)
This study aims to analyze the sampling technique using the Stratified Random method. Sampling samples in the study were 86 students. The results of self-efficacy research have a positive and significant effect on learning achievement. coefficients are 0.348241 and 0.355978, respectively. With tcount value of 2.070014 > ttable 1.69552 with significant value 0.0469 < = 0.05 and 2.798753 > ttable 1.68107 with value significant 0.0076 < = 0.05 which means Ha is accepted and Ho is rejected. The provision of rewards has a positive and significant effect on learning achievement. The coefficients are 0.379086 and 0.443925, respectively. Learning facilities have a positive and significant effect on learning achievement. coefficients are 0.150116 and 0.214942, respectively. Learning discipline has a positive and significant effect on learning achievement. coefficients are 0.184940 and 0.128583, respectively. family environment has a positive and significant effect on learning achievement. coefficients are 0.210983 and 0.172287, respectively. self-efficacy, giving rewards, learning facilities, learning discipline and family environment together have a significant effect on student achievement in economics class X Social Sciences SMA Negeri 4 Payakumbuh. Overall the value of Fcount 49.94751 > Ftable 2.33 and significant value 0.000 <α = 0.05, based on the sample group of high parental income, Fcount 11.58369 > Ftable 2.52 and significant value 0.000 <α = 0.05 and based on the sample group the income of parents is low, the value of Fcount is 24,80710> Ftable 2.43 and the significant value is 0.000 <α = 0.05. This means that Ha is accepted and Ho is rejected.